Antioxidant and Antibacterial Activity of Plectranthus scutellarioides (L.) R.Br. Ethanol Extract against Staphylococcus aureus - Anami Riastri; Yuliana Safitri; Azizah Amin (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2026)
Plectranthus scutellarioides (L.) R.Br., commonly known as Coleus scutellarioides, has been traditionally recognized for its medicinal properties, yet the synergy between its antioxidant capacity and its antibacterial efficacy against clinical pathogens, using modern extraction techniques remains limited and underexplored. This study aimed to evaluate the antioxidant activity and antibacterial efficacy of the ethanol extract of P. scutellarioides leaves against Staphylococcus aureus. The extract was obtained by ultrasonic-assisted extraction (UAE) using 96% ethanol as the solvent. Antioxidant activity was assessed through DPPH radical scavenging and ferric reducing antioxidant power (FRAP) assays. The antibacterial potential was determined by minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) using the dilution method. The ethanolic extract of P. scutellarioides exhibited antioxidant activity with an IC50 value of 154.54 ppm for DPPH and 146.47 ppm for FRAP assays, compared to vitamin C controls with IC50 values of 3.54 ppm and 3.57 ppm, respectively. Furthermore, the extract showed antibacterial activity against S. aureus with MIC and MBC values of 1.95 mg/mL and 3.90 mg/mL, respectively. These findings demonstrate that the ethanol extract of P. scutellarioides leaves possesses moderate antioxidant and significant antibacterial activities, highlighting its potential as a natural source for therapeutic agents. Contribution to Sustainable Development Goals (SDGs):SDG 3: Good Health and Well-BeingSDG 9: Industry, Innovation, and InfrastructureSDG 12: Responsible Consumption and ProductionSDG 15: Life on Land